THE INFLUENCE OF GOVERNMENT EXPENDITURE IN HEALTH AND EDUCATION ON POVERTY IN NORTH ACEH - Maisarah Maisarah; Cut Putri Melita Sari (LPPM Universitas Malikussaleh, 2020)
This study aims to determine the effect of government expenditure of health spending and education spending on poverty in North Aceh. This study uses time series data from 2008-2017. The study utilizes the Dynamic method using the Vector Autoregression model. The results can be seen that the government expenditure of health had no influence on poverty and the government expenditure of education had no effect on poverty in North Aceh in 2008-2017. Keywords:Government expenditure in the field of health, education, poverty.